Residual Bond Behavior of Steel Reinforced Recycled Aggregate Concrete After Exposure to Elevated Temperatures - Chen, Zongping; Zhou, Ji; Ban, Maogen; Wang, Xinyue (Frontiers in Materials, 2020)
As a frequent and serious disaster, the fire will cause serious damage to the building structure when it occurs, so it is very important to study the mechanical properties of structural components after a fire. In this paper, 20 push-out tests of steel reinforced recycled aggregate concrete (SRRAC) columns subjected to a fire were conducted in order to study the bond behavior between I-steel and recycled aggregate concrete (RAC) and the fire exposure was simulated by electrical oven . After this, the change of physical and mechanical properties and the process of mechanical failure of the specimens before and after high temperature exposure were analyzed, and the influence of various parameters on the bond behaviors of SRRAC subjected to elevated temperatures was discussed. At last, the calculation formulas of bond strength were put forward. Test results show that cracks appear on the surface of specimens when the maximum temperature is greater than 400°C, and the higher the temperature is, the more and wider the cracks are. With the increase of temperature, the bond strength of the specimen decreases significantly. When the replacement percentage of RCA is less than 50%, the bond strength increases continuously, on the contrary, the bond strength decreases, and the bond strength of RAC specimens is larger than that of natural aggregate concrete (NAC) specimens. Analysis on the development of bond damage after high temperatures exposure demonstrates that the higher the maximum temperature is, the slower the development of bond damage is. At the same time, the higher the maximum temperature is, the stronger the energy dissipation capacity is.